First-principles study on the electrical and thermal properties of the semiconducting Sc3(CN)F2 MXene. Issue 40 (19th June 2018) - Luo, Kan; Zha, Xian-Hu; Zhou, Yuhong; Guo, Zhansheng; Lin, Cheng-Te; Huang, Qing; Zhou, Shenghu; Zhang, Ruifeng; Du, Shiyu
Abstract : The two-dimensional semiconducting Sc3 (CN)F2 MXene presents relatively high carrier mobilities, specific heat and low thermal expansion coefficient from DFT calculations, and produces a good application prospect for nanoelectronic devices. Abstract : The two-dimensional materials MXenes have recently attracted interest for their excellent performance from diverse perspectives indicated by experiments and theoretical calculations. For the application of MXenes in electronic devices, the exploration of semiconducting MXenes arouses particular interest. In this work, despite the metallic properties of Sc3 C2 F2 and Sc3 N2 F2, we find that Sc3 (CN)F2 is a semiconductor with an indirect band gap of 1.18 eV, which is an expansion of the semiconducting family members of MXene. Using first-principles calculations, the electrical and thermal properties of the semiconducting Sc3 (CN)F2 MXene are studied. The electron mobilities are determined to possess strong anisotropy, while the hole mobilities show isotropy, i.e. 1.348 × 10 3 cm 2 V −1 s −1 along x, 0.319 × 10 3 cm 2 V −1 s −1 along the y directions for electron mobilities, and 0.517 × 10 3 cm 2 V −1 s −1 along x, 0.540 × 10 3 cm 2 V −1 s −1 along the y directions for hole mobilities. The room-temperature thermal conductivity along the Γ → M direction is determined to be 123–283 W m −1 K −1 with a flake length of 1–100 μm. Besides, Sc3 (CN)F2 presents a relatively high specific heat of 547 J kg −1 K −1 and a low thermal expansion coefficient of 8.703 × 10 −6 K −1 . Our findings suggest that the Sc3 (CN)F2 MXene might be a candidate material in the design and application of 2D nanoelectronic devices.